On the nano-additive enhanced flat plate solar collector integrated with thermal energy storage - Afolabi, L.O. (Bentham Science Publishers B.V., 2017)
Objective: Thermal efficiency of a flat plate solar collector incorporated with nanocomposite PCM-TES was experimentally studied in the present work. The augmentation of the PCM-TES, with nanocomposite, was examined to determine the ability of the collector to function after sunset, and over the night. Method: Outdoor experimental measurement involved three different operational modes; namely, measurement without TES, measurement with PCM-TES incorporated and measurement with nanocomposite-TES integration. Furthermore, the system performance in terms of extension of the period for hot water production at night time was determined. Conclusion: The experimental results revealed that the thermal efficiency was improved from 47.5 of without TES mode to 52.2 with PCM-TES mode. The nanocomposite-TES mode demonstrated increased thermal efficiency up to 57.5. The other indication of performance enhancement was the extended period of hot water production beyond day time operation. At 7.00AM the next day, the water temperature measurement with PCM-TES case was 39.5 °C and while with nanocomposite-TES case the water temperature measurement was 43.5 °C. The mode of PCM-TES integration extended the hot water production at night time by approximately 5 hours while with nanocomposite-TES mode; the hot water production period was further extended by approximately 7.0 hours. © 2017 Bentham Science Publishers.